The central-peripheral dichotomy and metacontrast masking. (August 2022) - Zhaoping, Li; Liu, Yushi
According to the central-peripheral dichotomy (CPD), feedback from higher to lower cortical areas along the visual pathway to aid recognition is weaker in the more peripheral visual field. Metacontrast masking is predominantly a reduced visibility of a brief target by a brief and spatially adjacent mask when the mask succeeds rather than precedes or coincides with the target. If this masking works mainly by interfering with the feedback mechanisms for target recognition, then, by the CPD, this masking should be weaker at more peripheral visual locations. We extended the metacontrast masking at fovea byEnns and Di Lollo to visual field eccentricities 1 ∘, 3 ∘, and 9 ∘ . Relative to the target's onset, the mask appeared at a stimulus onset asynchrony (SOA) of− 50, 0, 50, 92, or 142 milliseconds (ms). Enlarged stimuli were used for larger eccentricities to equalize target discrimination performance across eccentricities as best as possible for zero SOA and when SOA was too long for substantial masking. At each eccentricity, the masking was weakest at 0 or− 50 ms SOA, strongest at 50 ms SOA, and weakened with larger (positive) SOAs. Consistent with the CPD, larger eccentricities presented weaker maskings at all nonzero, and particularly the positive, SOAs.